THE ROLE OF THE FAMILY ENVIRONMENT IN THE FORMATION OF CHILD PSYCHOLOGY (Academicia Globe: Inderscience Research, 2021)
In today's evolving world, the concepts of family and children are becoming more and more abstract.Parents are not allocating enough time for their children. As a result, children develop a variety of bad habits and habits. This article provides some practical and theoretical advice on the role of parents in child-rearing.